(untitled) (KONFERENSIYA, 2025)
In this scientific paper, the semantic modeling of linguistic metaphor units is thoroughly studied in English and Uzbek. Metaphors have been described based on Lakoff and Johnson’s (1980) conceptual metaphor theory and a Kövecses (2005) cognitive semantic model through mapping between the source and target domain, conceptual structuring/structure, semantic extension mechanisms, and cultural aspects. The study takes the reader into extremely deep research into the commonalities, differences and culturally based peculiarities of metaphors that represent emotion, time, intellect, social relations and human character in English and Uzbek languages to a greater extent